Distinct Presynaptic and Postsynaptic Dismantling Processes of Drosophila Neuromuscular Junctions during Metamorphosis. - Liu, Z.; Chen, Y.; Wang, D.; Wang, S.; Zhang, Y.Q. (Journal of Neuroscience, 2010)
Synapse remodeling is a widespread and fundamental process that underlies the formation of neuronal circuitry during development and in adaptation to physiological and/or environmental changes. However, the mechanisms of synapse remodeling are poorly understood. Synapses at the neuromuscular junction (NMJ) in Drosophila larvae undergo dramatic and extensive remodeling during metamorphosis to generate adult-specific synapses. To explore the molecular and cellular processes of synapse elimination, we performed confocal microscopy, live imaging, and electron microscopy (EM) of NMJ synapses during the early stages of metamorphosis in Drosophila in which the expressions of selected genes were genetically altered. We report that the localization of the postsynaptic scaffold protein Disc large (Dlg) becomes diffuse first and then undetectable, as larval muscles undergo histolysis, whereas presynaptic vesicles aggregate and are retrogradely transported along axons in synchrony with the formation of filopodia-like structures along NMJ elaborations and retraction of the presynaptic plasma membrane. EM revealed that the postsynaptic subsynaptic reticulum vacuolizes in the early stages of synapse dismantling concomitant with diffuse localization of Dlg. Ecdysone is the major hormone that drives metamorphosis. Blockade of the ecdysone signaling specifically in presynaptic neurons by expression of a dominant-negative form of ecdysone receptors delayed presynaptic but not postsynaptic dismantling. However, inhibition of ecdysone signaling, as well as ubiquitination pathway or apoptosis specifically in postsynaptic muscles, arrested both presynaptic and postsynaptic dismantling. These results demonstrate that presynaptic and postsynaptic dismantling takes place through different mechanisms and that the postsynaptic side plays an instructive role in synapse dismantling.